The Region Centromeric to HLA-C Is a Key Region for Understanding the Phenotypic Variability of Psoriatic Arthritis. (30th January 2014) - Queiro, Rubén; Tejón, Patricia; Alonso, Sara; Coto, Pablo; López-Larrea, Carlos; Martínez-Borra, Jesús; González, Segundo
Abstract : With the aim of clarifying the role of several polymorphisms around the HLA-C locus in the clinical expression of PsA, the distribution of several polymorphic markers and genes located around the HLA-C locus was analyzed in a well-established cohort of 110 patients with PsA, 50 patients with psoriasis alone, and 110 healthy controls. The frequency of these genes was also analyzed by PsA articular models, based on three main subgroups: oligoarthritis, polyarthritis, and spondylitis. Distal interphalangeal joint (DIP) involvement was associated with the presence of MICB-CA20 (OR 6.0, 95% CI: 1.58–22.69, P = 0.005 ). HLA-DRB * 07 was associated with oligoarticular forms of PsA (OR 4.1, 95% CI: 1.8–9.3, P = 0.00 07 ). The spondylitic forms overexpressed the antigen HLA-B * 27 (OR 5.7, 95% CI: 2.4–13.6, P = 0.00 01 ). MICA-A5.1 showed association with polyarthritis (OR 3.7, 95% CI: 1.5–8.8, P = 0.00 6 ). Genes telomeric to HLA-C were overexpressed in psoriasis but not in PsA subphenotypes. This study shows that the region centromeric to HLA-C is a key region that expresses not only disease risk genes but also genes that help explain the phenotypic variability of PsA.